The Efficacy of Deep Cervical Flexor Training with Feedback Reducing Pain and Disability in Individuals with Work-Related Neck Pain - I Dewa Gede Alit Kamayoga; A A I Ayesa Febrinia Adyasputri; I Putu Yudi Pramana Putra; M. Widnyana; Anak Agung Gede Eka Septian Utama (Physical Therapy Journal of Indonesia, 2021)
Introduction: The most common trouble when doing task is work related neck pain. Neck pain can have negative effect on workers related to the resulting work productivity. To conquer this, there is deep cervical flexor training with feedback training to solve that problems. This study aims to find out whether deep cervical flexor training with feedback is powerful in reducing pain and disability the work-related neck pain. Methods: This study using a literature review by conducting data studies related to deep cervical flexor training with feedback, neck pain, and working. The initial search in 4 databases found a total of 36 articles. After the selection using inclusion and exclusion criteria obtained 28 articles. Results: Based on some literature, it shows that deep cervical flexor training with feedback aims to activate the deep cervical flexor muscle effectively in reducing pain through the release of endorphins and decreasing pain and changes in muscle function have an effect on reducing disability in work related neck pain. Conclusion: Providing deep cervical flexor training with feedback is powerful in decreasing the level of pain and disability in work-related neck pain.